Folate supplementation as a strategy to reduce Neural Tube Defects - Jha, Shreya; Kant, Shashi (Indian Journal of Community Health, 2022)
Folic acid is a vitamin known to prevent neural tube defects, megaloblastic anaemia, cardiovascular morbidity and mortality, etc. The main natural sources of folate are plant and vegetables e.g. green leafy vegetables, broccoli, asparagus, citrus fruits (orange, strawberry), beans, nuts, cauliflowers, beets, corn etc. and meat products like liver. The primary function of folate is its contribution in the synthesis and repair of the DNA. The bioavailability of food folate is approximately 50%. The bioavailability of folic acid taken with meal compared to with water on empty stomach is 85% and 100% respectively.(1) Hence, it is easier to achieve the recommended daily allowances with fortified food as compared to natural food due to higher stability and bioavailability of synthetic folate when compared to natural food.(2)